Penerapan Pembelajaran Tipe Jigsaw untuk Meningkatkan Aktivitas Siswa dalam Pembelajaran IPA di Kelas VII-8 SMP Negeri 7 Bukittinggi - Nilawati Nilawati (Journal on Education, 2023)
This study aims to find out whether the Jigsaw type learning model can increase the science learning activities of class VII-8 students of SMP Negeri 7 Bukittinggi in the 2016/2017 academic year. This type of research is class action research, which aims to improve science learning activities Physics students of class VII-8 SMPN 7 Bukittinggi. This research was conducted in 2 cycles. The instrument used is an observation sheet, student learning outcomes. The results of the observations were then analyzed and used as material for action planning for the next cycle in order to draw conclusions. The findings of this study after being analyzed showed that based on the results of the first cycle of student activity in carrying source books/readings 50.3%, collaboration in groups 59.6%, issuing opinions in the large group 35.7%, working on questions in groups 45.7%, pointing hands answering quizzes 24%. Whereas in the second cycle there was a significant increase, in the aspect of bringing source books/readings 67.5%, cooperation in groups 74%, expressing opinions in large groups 59%, working on problems in groups 76%, and pointing hands answering quizzes 65% . This shows that the activities of class VII-8 students in the odd semester of the 2016/2017 academic year are in good condition. In general, from the results of the analysis of the data, it can be concluded that the Jigsaw type learning model of student learning activities in learning science has increased.